Parasites and parasitic diseases of the camel in India: a review - PATHAK, K M L; CHHABRA, M B (The Indian Journal of Animal Sciences, 2010)
The camel (Camelus dromedarius L.) is subject to several parasites belonging to all 3 major groups, viz. protozoa, helminths and arthropods. Some of them are regularly associated with disease and have consequently been studied in depth. These include the protozoan Trypanosoma evansi, the cause of trypanosomosis, which ranks as probably the most serious infectious disease of camels. Gastrointestinal nematodes (GIN), particularly the stomach worm Haemonchus, have compelled the maximum attention due to pathogenicity. Sarcoptic mange is not only widely prevalent in India, but is a serious, debilitating and dreaded disease. An overwhelming majority of literature in India, following international trend, has been devoted to these 3 entities of parasitic diseases. Reports and research publications in recent years, indicate considerable advancements in various aspects, particularly in the diagnostic techniques for trypanosomosis, epidemiology and control of GIN and acaricidal therapy for sarcoptic mange. Other parasites in each category, less frequently reported, but potentially capable of adversely impacting the camel economy through morbidity and occasional disease, such as coccidia, hydatidosis, myiasis and tick infestations, have also been included in the review. Attempts were also made to define the existing information gaps and to identify the topics for inclusion in future investigations and surveillance of camelid parasites.